Efeito do álcool e formol sobre a composição isotópica de δ 13C e de δ 15N em Plagioscion squamosissimus e Hypophthalmus edentatus (Pisces, Osteichthyes) - Manetta, Gislaine Iachstel; Benedito, Evanilde; Ducatti, Carlos [UNESP] (Universidade Estadual de Maringa, 2011)
The present study investigates the δ 13C and δ 15N isotopic composition in frozen samples (control), samples in alcohol and in formaldehyde of Plagioscion squamosissimus and Hypophthalmus edentatus. From each individual we extracted a strip of muscle from the region above the lateral line, in the dorsal fin base, that was divided into three equal parts, each one was submitted to one type of treatment: freeze - control group (-15oC), conservation in alcohol 70% and fixation in formaldehyde 4%. Samples were kept under those treatments for 30 days, washed and submerged in distilled water for 4 hours. Afterwards, they were dried up in air oven at 60oC for 48 hours and macerated until the obtaining of a fine powder. A significant difference was found in isotopic values of carbon and nitrogen, between the control and the samples in alcohol and formaldehyde, except for δ 13C from the H. edentatus samples in formaldehyde. The carbon isotopic values of samples in alcohol were mostly enriched compared to control, whereas the samples in formaldehyde presented depleted values in relation to the control. The nitrogen isotopic values for both samples preserved in alcohol and formaldehyde were enriched when compared to the values of frozen samples, independently of used preservatives. Therefore, the isotopic correction should be accomplished according to the isotope and preservative employed for species of freshwater fish.
Effect of alcohol and formaldehyde on the δ 13C and δ 15N isotopic composition of Plagioscion squamosissimus and hypophthalmus edentatus (Pisces, Osteichthyes)
Keywords: Fishes; Hypophthalmus edentatus; Plagioscion squamosissimus; Preservative; Stable isotope; alcohol; carbon; carbon 13; delta carbon 13; delta nitrogen 15; formaldehyde; nitrogen; nitrogen 15; unclassified drug; animal tissue; controlled study; fish; freezing; nonhuman; preservation; Osteichthyes; Pisces